Knut Hamsun—stemningsdikter - Nordøy, Atle Tord (Nordlit, 2016)
In this essay I take a closer look at the Norwegian concept of stemning, and how this concept has been applied to Hamsun’s early work. I look at both the semantics and the history of the concept, and at Hamsun’s own use of it. The main insight of this investigation is that stemning is a concept that is not limited to subjective or objective experience, but must be understood outside of the object/subject dichotomy. These insights are then used in an analysis of Hamsun’s short story, ”Onde dage”, where I show that Hamsun is not trying to capture a subjective experience, but a common human reality.